Factors Affecting The Use Of Gamification In Online Learning Environment Among School Teachers In The Kingdom Of Saudi Arabia - Ayed S, Alosaimi Mutlaq (2023)
The use of technology and e-learning systems in classrooms can have a significant impact on students’ learning. Not to be left behind, the Saudi government launched the ‘Future Gate’ project to implement technology in secondary schools in which gamification is applied in this e-learning platform. However, what are the factors that might influence its acceptance and utilization among the school teachers? Specifically, this study examined the effects of performance expectancy, effort expectancy, social influence, hedonic motivation, facilitating conditions, and habit on teachers’ behavioural intention to use gamification in teaching and learning activities in the Future Gate platform. It also investigated the impact of age, gender, and experience on these variables. In addition, the study evaluated the effects of task and technology characteristics and how they influence teachers’ perception of Task-Technology Fit (TTF) and the teachers’ behavioural intention to use gamification. This study utilised SEM-Partial Least Square (PLS-SEM) to analyse the relationships between the constructs identified from the literature review. A total of 328 secondary school teachers participated in this study from seven districts in Saudi Arabia.